Randomised multicentre trials of CHART vs conventional radiotherapy in head and neck and non-small-cell lung cancer: an interim report. CHART Steering Committee. - Saunders, M. I. (Nature Publishing Group, 1996)
While radiotherapy is proceeding, tumour cells may proliferate. The use of small individual doses reduces late morbidity. Continuous hyperfractionated accelerated radiation therapy (CHART), which reduces overall treatment from 6-7 weeks to 12 days and gives 36 small fractions, has now been tested in multicentre randomised controlled clinical trials. The trial in non-small-cell lung cancer included 563 patients and showed improvement in survival; 30% of the CHART patients were alive at 2 years compared with 20% in the control group (P = 0.006). In the 918 head and neck cases, there was only a small, non-significant improvement in the disease-free interval. In this interim analysis there was a trend for those with more advanced disease (T3 and T4) to show advantage; this will be subject to further analysis when the data are more mature. The early mucosal reactions appeared sooner and were more troublesome with CHART, however they quickly settled; so far no difference in long-term morbidity has emerged. These results support the hypothesis that tumour cell repopulation can occur during a conventional course of radiotherapy and be a cause of treatment failure.